Protocol for a two-clone system to study signaling interactions among neuronal cells in a pre-clinical Alzheimer’s disease model - Aditi Singh; Prajakta Deshpande; Ankita Sarkar; Catherine Yeates; Anuradha Venkatakrishnan Chimata; Madhuri Kango-Singh; Amit Singh (STAR Protocols)
Summary: This protocol outlines a two-clone genetic mosaic approach in Drosophila to study cell signaling using the FLP/FRT (Flippase/Flippase recombination target) and Gal4/UAS (upstream activating sequence)/Gal80 systems. We generated a stable transgenic line expressing human Aβ42, and then we crossed it with a GFP-marked FRT line to produce mosaic clones via heat-shock-induced recombination. Then we dissected, stained, and imaged the eye discs to visualize wild-type and mutant clones. Image analysis with Fiji/ImageJ and statistical quantification in GraphPad Prism enable the study of cell competition and intercellular signaling mechanism(s) in human diseases.For complete details on the use and execution of this protocol, please refer to Yeates et al. and Tare et al.1,2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.